Shaping Illocutionary Force through Pragmatic Markers in Nosedive (Black Mirror, 2016) - Malika Latif Nugroho; Dedi Sulaeman; Erlan Aditya Ardiansyah (The Study Program of English Education of Palangka Raya University, 2026)
Although speech acts and pragmatic markers are both central to meaning-making in interaction, most previous research has examined them separately, leaving a gap in understanding how they function together to shape illocutionary force in socially sensitive communication. This study addresses that gap by exploring how pragmatic markers shape the illocutionary force of speech acts in Nosedive (Black Mirror, 2016), a fictional context in which a social rating system intensifies the pressure on speakers to manage politeness, image, and interpersonal approval. Using a qualitative descriptive approach, 178 utterances were purposively selected from the episode transcript and analyzed using Searle's (1969, 1979) speech act classification and Fraser's (1996) pragmatic marker framework. The findings show that discourse markers are the most dominant category, appearing through markers such as well, but, so, I mean, and you know to organize discourse, signal contrast, and elaborate meaning, while commentary markers such as just, sorry, um, and uh soften the force of utterances and reduce face-threatening acts. Parallel markers signal interpersonal stance, and basic markers signal illocutionary force directly through performative expressions. This study contributes to pragmatic studies by showing that pragmatic markers do not merely organize discourse but also actively adjust the perceived force of speech acts in socially evaluative interaction.